THE SOLUTION TO SOCIETAL ISSUES IN THE CONTEMPLATION OF THE QURAN AND THE ROLE OF ISLAMIC LAW - Dr.Nisar Mehmood; Ms. Salma Bib (Journal of Religion and Society, 2025)
The research is a critical analysis of the role played by Tadabbur-e-Quran (deep reflection on the Quran) in solving collective problems of the society, specially the role played by the Islamic law in shaping an organized and just society. The work relies on exegetical approach of Maulana Amin Ahsan Islahi, whose tafsir, Tadabbur-e-Quran, considers the Quran a self-consistent system of Godly guidance. Islahi views the Quran not as a means of personal piety, but as a comprehensive program of the reformation of society. The approach highlights contextual knowledge, goals of Shari ah and critical thinking, and, therefore, provides applicable solutions to current issues. The present paper will discuss the ways in which Quran deals with basic social values, including justice (adl), mercy (rahmah), and piety (taqwa) and how those values can be applied in accordance with the Islamic law. It also discusses the Quranic ideas of human vicegerency (khilafah), a notion of the whole Muslim Ummah as witness of mankind and the values of the social equilibrium. The research shows the practical application of divine guidance in community life through the analysis of Quranic instructions regarding family systems, economic justice (e.g. zakat and prohibition of riba), criminal laws (as hudud and ta does not mean the same thing as hudud and ta continuum) and governance (e.g. shura and accountability). The interplay between ethics, law, and spiritual education is also pointed out in the paper with the emphasis that the objectives of Islamic rulings go beyond enforcement of law, but they also seek to develop the character and reform the morals. It emphasizes the significance of maqasid al-shari, that is, objectives of Islamic law, and the necessity to have ijtihad (independent reasoning) in applying Quran laws to the contemporary condition. The examples of the Islamic economic model, criminal justice, minority rights, gender equity, and other cases shown in the study make it clear that Qur an present timeless and universal fundamentals that, once interpreted through critical thinking and implemented in the context, can help the world achieve a well-balanced and fair society. Keywords: Tadabbur-e-Qur’an, Islamic Law, Maulana Amin Ahsan Islahi, Social Justice in Qur’an, Maqasid al-Shari‘ah, Qur’anic Legal System, Ijtihad and Modern Application